2008
DOI: 10.1080/10810730802487471
|View full text |Cite
|
Sign up to set email alerts
|

Entertainment-Education in a Media-Saturated Environment: Examining the Impact of Single and Multiple Exposures to Breast Cancer Storylines on Two Popular Medical Dramas

Abstract: In the United States, entertainment-education (E-E) initiatives in primetime television that provide public health information are at risk for diminished impact due to the media-saturated environment in which they must compete. One strategy to overcome this limitation is to use multiple primetime TV shows to reinforce similar health messages in multiple storylines. The current study explores such an approach by evaluating the impact of two separate breast cancer genetics storylines featured on two different TV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 25 publications
3
63
0
2
Order By: Relevance
“…En este sentido, esta investigación sirve para corroborar la importancia del edu-entretenimiento como herramienta para enfrentarse a retos socio-sanitarios (Moyer-Gusé, 2008;Igartua & Vega, 2014). Se sitúa así en la línea de otros estudios que recurren al análisis de los dramas médicos en su función de educación-entretenimiento (Hether et al, 2008) y, en general, señalan el potencial del entretenimiento televisivo para educar en relación a los asuntos sanitarios (Brodie et al, 2001;Sharf, Freimuth, Greenspon & Plotnick, 1996;Larson, 1991).…”
Section: Conclusiones Y Discusiónunclassified
“…En este sentido, esta investigación sirve para corroborar la importancia del edu-entretenimiento como herramienta para enfrentarse a retos socio-sanitarios (Moyer-Gusé, 2008;Igartua & Vega, 2014). Se sitúa así en la línea de otros estudios que recurren al análisis de los dramas médicos en su función de educación-entretenimiento (Hether et al, 2008) y, en general, señalan el potencial del entretenimiento televisivo para educar en relación a los asuntos sanitarios (Brodie et al, 2001;Sharf, Freimuth, Greenspon & Plotnick, 1996;Larson, 1991).…”
Section: Conclusiones Y Discusiónunclassified
“…Wilkin et al, 2007) as a means to influence viewers' knowledge, attitudes, and behaviour regarding social concerns. E-E has been shown to be successful in changing attitudes and behaviour with respect to a number of issues, including family planning , HIV prevention , breast cancer screening (Hether et al, 2008;Wilkin et al, 2007), domestic violence (Usdin et al, 2004), and dowry payments (Papa et al, 2000). Moyer-Gusé (2008) explains that E-E works through narrative engagement as well as the identification with and emulation of characters that is predicted by social cognitive theory.…”
Section: Introductionmentioning
confidence: 99%
“…Papa et al, 2000;Wray et al, 2004), television dramas (e.g. Hether et al, 2008), and telenovelas (e.g. Wilkin et al, 2007) as a means to influence viewers' knowledge, attitudes, and behaviour regarding social concerns.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the breast cancer storylines was to increase knowledge about the mutations and to encourage breast cancer screening. A study showed that these storylines indeed influenced recipients' knowledge, attitudes, intentions, and behaviors as intended (Hether, Huang, Beck, Murphy, & Valente, 2008).…”
mentioning
confidence: 99%